Waves of Extremism: An Applied Ethnographic Analysis of the Bosnia and Herzegovina Football Terraces - Testa, Alberto (Frontiers in Sports and Active Living, 2022)
This article offers an overview of a four-month research project, conducted in 2019/2020, which studied extremism in the Bosnia and Herzegovina (BiH) football terraces. This work was funded by the International Organisation for Migration - United Nations and by the United States Agency for International Development (USAID). The research focused on risk factors and how these may govern the “entry” of BiH youth into extreme hard-core football fans groups (Ultras1) and prolong their involvement in them. The study highlighted the nature of these groups and their activity providing detailed recommendations for BiH policymakers, security agencies, and football federations and clubs who wish to understand and effectively respond to this emergent threat for public security in BiH.